Training for Fluency and Generalization of Math Facts Using Technology. (November 2015) - Musti-Rao, Shobana; Lynch, Tom Liam; Plati, Erin
As American students struggle with basic mathematical skills, the importance of math fact fluency has gained the attention of educators and researchers. Generalization of math fact fluency is also important for the transfer of skills to other settings and formats, assisting students in the completion of more varied and complicated math tasks. This column explores technology in the classroom and use of mobile applications (i.e., apps) to train students in fluency and generalization of math facts. Key features of apps that teachers should consider for classroom use are described and ways in which apps can provide students with a variety of stimulus and response conditions to promote fluency and generalization of math facts are highlighted.